A late Cretaceous fagalean inflorescence preserved in amber from New Jersey. Issue 8 (14th June 2018) - Gandolfo, Maria A.; Nixon, Kevin C.; Crepet, William L.; Grimaldi, David A.
Abstract : Premise of The Study: An inflorescence with three pistillate flowers in amber from the early Upper Cretaceous (Turonian, ~90–94 million years ago) of central New Jersey represents the oldest known flowers with features present in an early stem complex of the Fagales. The inflorescence has characteristics of Nothofagaceae, but also has strikingly distinct characters that suggest it is intermediate between Nothofagus and other Fagales. This intermediacy is consistent with its northern hemisphere distribution. Methods: We investigated this new fossil by comparing it with extant and fossil members of the Fagales using light microscopy and nano‐computed tomography. In addition, for exploring its relationships, we mapped the morphological characters onto a widely accepted molecular‐based tree of modern basal Fagales using standard methods of character optimization. Key Results: The phylogenetic position of the fossil inflorescence can be unequivocally determined by the presence of unique features, singly and in combination, that are found only in "basal" members of Fagales. The fossil adds critical information on the features of the early stem Fagales, evolution of the cupule in Nothofagaceae and Fagaceae, and a reasonable biogeographic hypothesis for the differentiation of southern (e.g., Nothofagaceae) and northern hemisphere Fagales. Conclusions: This new fossil provides insight into the early evolution of Fagales and suggests that early stem Fagales that had not yet differentiated into modern families were present in the Late Cretaceous of North America. Based on available evidence, the fossil is best interpreted as an early stem member of the Fagales, with features that suggest a transition from a more generalized Nothofagus ‐like fagalean ancestor with some unique presumably plesiomorphic features. The presence of an enlarged perianth and flexuous styles also suggests the possibility of insect pollination, which has been lost in all Fagales with the exception of some members of subfamily Castaneoideae in Fagaceae sensu stricto (which otherwise are very different from this fossil). The poorly developed, bract‐like cupule valves of the fossil can be interpreted as primitive (i.e., incipient) or as reduced from more developed cupules that are found in most modern Fagaceae and Nothofagaceae.